2014
DOI: 10.3329/sja.v11i1.18389
|View full text |Cite
|
Sign up to set email alerts
|

Response of nitrogen fertilization on Bt and non-Bt cotton (Gossypium hirsutum) hybrids

Abstract: A field experiment was conducted during 2006 and 2007 (June- December) at New Delhi to assess the performance of three cotton hybrids of which two Bt (MRC 6304 & RCH 317) and one non-Bt cotton hybrid LHH 144 (North zone check) in response to nitrogen fertilization (0, 60, 120 and 180 kg ha-1). Based on pooled analysis, both Bt hybrids produced similar seed cotton yield (SCY). Bt hybrid have produced 7.1 bolls/plant (on an average) and bolls 0.48 g heavier than non Bt hybrid LHH 144 that lead to 1.07 t ha-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 5 publications
(3 reference statements)
3
8
0
Order By: Relevance
“…The probable reason for this might be the variation in the genetic constitution of the cultivars which has responded better in plant height. These results were in closer conformity with the findings of Manjunatha et al, (2010) and Gangaiah et al, (2013).…”
Section: Effect Of Bt Genesupporting
confidence: 83%
“…The probable reason for this might be the variation in the genetic constitution of the cultivars which has responded better in plant height. These results were in closer conformity with the findings of Manjunatha et al, (2010) and Gangaiah et al, (2013).…”
Section: Effect Of Bt Genesupporting
confidence: 83%
“…In a 2-year experiment conducted at New Delhi in a soil similar to that in the current study, Gangaiah et al (2013) reported that pooled seed cotton yield of Bt cotton hybrids increased by applying N up to 120 kg N ha -1 . Nitrogen application beyond the optimum level in cotton may reduce the yield (Wood et al, 1992) due to rank growth and decreases in the harvest index (Bouquet et al, 1994).…”
Section: Discussionsupporting
confidence: 65%
“…However, none of the previous studies could determine the proportionate contribution of fertilizers in increasing the cotton yield in India during the BT phase. Besides, BT cotton hybrids showed better nitrogen use efficiency and also responded well to the increased N application as compared to non-BT hybrids (Gangaiah et al, 2013). Therefore, increase in the yield of cotton in India during the BT phase could be due to the cultivation of nitrogen responsive Bt hybrids.…”
Section: Discussionmentioning
confidence: 93%
“…However, response of cotton yield to Napplicationwas found to have quadratic relationship and showed maximum peak @ 180kg/ha (Gangaiah et al, 2013). Besides, higher dose of fertilizers has been reported to increase the population of sucking pests in cotton (Kalaichelvi, 2008).Thus, the observed reduction in PFP of cotton from 2009 to 2014 in India might be due to the higher dose of fertilizer application, i.e.…”
Section: Discussionmentioning
confidence: 98%